Ar-Enhanced Reading Instruction: Impact on Indonesian EFL Learners' Comprehension and Attitudes - Mustakim Sagita; Issy Yuliasri; Abdurrahman Faridi; Hendi Pratama (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2025)
This study investigates the effects of Augmented Reality (AR) books on the reading comprehension and attitudes of Indonesian EFL learners. Employing a quasi-experimental mixed-method design, 62 university students were divided into an experimental group (n=31) and a control group (n=31). Over a five-week intervention, the experimental group used AR books via tablets, while the control group used printed textbooks. Reading comprehension was assessed using pre- and post-tests, and attitudes were measured using a validated reading attitude questionnaire. Qualitative data were gathered through semi-structured interviews with participants from the experimental group. The results revealed a statistically significant improvement in reading comprehension for the AR group (t(13)=4.73, p < 0.001, CohenÔÇÖs d = 0.83), and significantly more positive reading attitudes across all measured domains (e.g., overall attitude: t(60)=3.48, p = 0.002). These findings suggest a large effect size and practical benefit of AR book integration. The study highlights the potential of AR technology to enhance both cognitive and affective outcomes in EFL reading instruction and supports its implementation in digitally supported learning environments.